Données préliminaires concernant la reproduction artificielle chez le flet (platichthys flesus luscus) (pallas) - Udrea, Valerian (Cercetări Marine - Recherches Marines, 2026)
Experiments of artificial reproduction of flounder (Platichthys flesus luscus) showed the species can reach natural maturation in captivity conditions without any stimulus. Eggs fecundation by the dry method combined with the water one gives the best results. At 8.18OC medium temperature the spawning occurs in 10 days. It is not advisable to feed the larvae after the vitellin purse resorption by Artemia salina eggs, those being hardly digestible can cause the death of organisms.